Peran taman bacaan hendra sebagai fungsi pendidikan untuk masyarakat - Sinthia Rahmi (Nautical : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This study discusses the role of Community Reading Gardens as an educational function for the community. The purpose of this study is to find out how the role of Hendra Reading Gardens is in providing learning resources, information sources and educational recreation for the community. The method used is a qualitative research method with a case study approach, data collection techniques are carried out by conducting interviews, library research, observation and documentation. This study uses the Guidebook for Norms, Standards, Procedures, and Criteria for Community Reading Gardens in 2013, in which Community Reading Gardens have an important role as an educational function. The informants in this study consisted of 8 (eight) people who were interviewed, two people were managers and six people were members of the Hendra Reading Gardens. The results of this study indicate that the role of the Hendra Reading Gardens in Cihapit District, Bandung City is very instrumental in the community by providing learning resources, information sources, and recreation, and the community can develop learning potential through the provision of a collection of reading materials held by Hendra Reading Park. The conclusion that can be drawn from this research is that Hendra Reading Park is very helpful in empowering the community to like reading, giving a positive impact on the surrounding environment in advancing the function of education for the community.